Peristaltic transport of blood in terms of casson fluid model through a tube under impact of magnetic field for moderate reynolds number - Ahmed, Bilal; Javed, Tariq; Muhammad Sajid (Penerbit Universiti Kebangsaan Malaysia, 2018)
The effect of moderate non-zero Reynolds number on the nonlinear peristaltic transport of a blood flow through narrow arteries, where blood flow behaves similarly as a Casson fluid under the externally applied uniform magnetic field is investigated numerically. The governing equations for blood flow model of Casson fluid are formulated to a system of nonlinear coupled partial differential equations, which are exposed to Galerkin’s finite element method. The assumptions of lubrication theory are neglected, due to which the effects of moderate Reynolds number and wave number along with other parameters are presented. To ensure the accuracy of developed code, obtained results are compared to that of available results in the literature and found in excellent agreement. The analysis shows that increasing Reynolds and Hartmann numbers enhance the velocity of the fluid. One of the findings of this study is the nonlinear behavior of pressure rise for large values of Reynolds and Hartmann numbers. Increasing wave number enhances the pressure rise in the peristaltic pumping region. The study also discussed to effect of Casson fluid parameter and time mean flow through graphs of velocity, pressure rise and contours of streamlines.